Olympic snow sports: current insights and future directions for Milano Cortina 2026 and beyond - Zoppirolli, C.; Fornasiero, A.; Spörri, J.; Losnegard, T.; Elfmark, O. A.; Sandbakk, Ø.; Holmberg, H.-C. (Scandinavian Journal of Medicine & Science in Sports, 2026)
As the Milano Cortina 2026 Winter Olympic Games approach, a comprehensive understanding of performance determinants across Olympic snow sports is increasingly important to further evolve training and performance. However, the scientific literature remains unevenly distributed, with well-established knowledge in cross-country skiing, biathlon, and alpine skiing, and limited data in disciplines such as ski mountaineering, freestyle skiing, snowboarding, ski jumping, and Nordic combined. This narrative review synthesizes current evidence to (1) identify key performance-determining factors, (2) describe discipline-specific training characteristics, and (3) highlight critical knowledge gaps. Regarding performance determinants, Olympic snow sports can be broadly categorized into endurance-dominant disciplines (e.g., cross-country skiing, biathlon, ski mountaineering), which rely on high aerobic capacity and movement efficiency, and the gravity and technical disciplines (e.g., alpine skiing, freestyle skiing, snowboarding, ski jumping), which emphasize neuromuscular power and technical precision. Nordic combined represents a hybrid of these categories. In terms of training characteristics, elite athletes' training models reflect sport-specific demands through tailored combinations of endurance, strength-power, technical, tactical, and psychological preparation. Finally, regarding knowledge gaps, sex-specific analyses of physiological profiles, biomechanics, and training responses remain scarce, particularly in gravity and technical sports. Furthermore, standardized documentation of training structure, integration of on-snow monitoring technologies, and research on energy availability remain underdeveloped. Addressing these gaps through holistic, multidisciplinary research is essential to develop individualized, sex-informed, and evidence-based frameworks that support athlete development and performance optimization in the lead-up to Milano Cortina 2026 and future Olympic cycles.